Study on scatter of surface integrity of bearing raceway grinding - Chang, Zhou; Hu, Lai (Manufacturing Technology Journal, 2022)
Taking the discrete degree of bearing raceway grinding surface integrity as the research object, the orthogonal test based on the wheel speed, workpiece speed and grinding depth is designed. The residual stress, retained austenite, hardness, grinding modified layer thickness and roughness of the raceway after grinding test were measured, and the mean value and standard deviation of these indexes were calculated. The results show that the standard deviation of residual stress and roughness decreases with the increase of wheel speed, and the standard deviation of retained austenite, hardness and grinding modified layer thickness keeps stable. Finally, the optimal grinding parameters considering the scatter of surface integrity are selected.
Keywords: raceway grinding; surface integrity; orthogonal test; scatter; standard deviation